Examining inflation and economic growth in Tunisia: An ARDL approach - Soltani, Hassen (International Journal of Innovative Research and Scientific Studies, 2025)
The aim of this paper is to examine the impact of inflation on the growth of the Tunisian economy over three decades (1991–2023). The study implemented the ARDL approach to capture both the short- and long-term interactions. Ultimately, a negative inflation-economic growth relationship emerged and was estimated at -0.85. These estimates illustrate that the presence of inflation substantially lowers the purchasing power of the public, which subsequently distorts investment tendencies and leads to macroeconomic instabilities. In the case of short-run outcomes, the results show that inflation from prior years has a lagged effect on economic growth. Better put, moderate amplifications in price levels may serve to positively bolster economic endeavors until such a time that the adverse ramifications begin to overshadow, at which point the economy will start to shrink. The employer side of the economy also led to increases in short-run growth due to labor force participation, but the level of investment in GFCF suggests an underlying inefficiency in long-run investment growth. They were also able to observe certain integrations in the variables, which suggested that long-run relationships exist. However, the pace at which these nominal variables are able to adjust within the period significantly varies at 88.64%. The results of this examination indicate the need for an inflation level of moderate intensity together with structural changes to achieve an investment multiplier and gain in labor productivity. This analysis may assist policymakers in formulating policies for Tunisia designed for inflation control and sustainable economic growth, which are key components of Tunisia’s development goals.